The think big manifesto : think you can't change your life (and the world)? Think again - Port, Michael, 1970-; Samuels, Mina. (Hoboken, N.J. : John Wiley, 2009)
Think Bigger. About Who You Are. And What You Offer the World. Stand for something before someone stands on you. Revolt against the play-it-safe, don't disturb the peace, cynical and silenced society that, more often than not, buries big thoughts. Michael Port, bestselling author and creator of ThinkBigRevolution.com, knows it's not always easy to think big. But big thinking must happen now; today, tomorrow, and forevermore. At this very moment, you are the change you want to see in the world--should you choose to accept personal responsibility. Devour every word of The Think Big Manifesto. It.
We are more than we know -- You say you want a revolution -- This thing called thinking big -- Statement of the think big revolution -- The case for big thinking (or the case against small thinking) -- The code (join the revolution in progress or start your own) -- When--is now.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Achievement motivation; Performance; Performance technology; Task Performance and Analysis; Motivation d'accomplissement.; Rendement au travail; SELF-HELP -- Personal Growth -- Success; SELF-HELP -- Personal Growth -- Happiness; SELF-HELP -- Personal Growth -- General; PSYCHOLOGY -- Applied Psychology; Performance technology; Achievement motivation; Performance; Motivation (Psychology); Performance